Enhancing professional practice : a framework for teaching - Danielson, Charlotte (Alexandria, Va. : Association for Supervision and Curriculum Development, 1996)
A framework for teaching based on the PRAXIS III: Classroom Performance Assessments criteria identifies those aspects of a teacher's responsibilities that have been documented through empirical studies and theoretical research as promoting improved student learning.
Includes bibliographical references
Keywords: Teaching; Classroom environment; Educational planning